2016
DOI: 10.4236/jeas.2016.61004
|View full text |Cite
|
Sign up to set email alerts
|

Precision Synthesis of a Long-Chain Silane Coupling Agent Using Micro Flow Reactors and Its Application in Dentistry

Abstract: In dentistry, a wide range of materials is available for restorative treatment; a typical product of such restorative materials mainly consists of radically polymerizable monomer(s) and inorganic filler(s) (for added physical strength), as well as a surface modifier (e.g. silane coupling agent) for improved affinity between monomer and filler. It is favorable to use an optimal surface modifier depending on the respective restorative materials. However, commercially available surface modifiers, which are synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
4
6
0
Order By: Relevance
“…The nding reiterates that of an earlier study performed on silanes with a 10-carbon hydrocarbon chain which was able to better resist hydrolytic degradation than MPS [18]. Another study found that by virtue of a long hydrocarbon chain length, experimental resin composites synthesised with MOS exhibit lower viscosity while having higher exural modulus and strength and being less brittle than MPS [21]. This may be explained by the 'restrained layer theory', whereby silanes between the inorganic substrate and resin polymer matrix are capable of deformation and act as a stress breaker [22].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The nding reiterates that of an earlier study performed on silanes with a 10-carbon hydrocarbon chain which was able to better resist hydrolytic degradation than MPS [18]. Another study found that by virtue of a long hydrocarbon chain length, experimental resin composites synthesised with MOS exhibit lower viscosity while having higher exural modulus and strength and being less brittle than MPS [21]. This may be explained by the 'restrained layer theory', whereby silanes between the inorganic substrate and resin polymer matrix are capable of deformation and act as a stress breaker [22].…”
Section: Introductionsupporting
confidence: 83%
“…Three-point bending test is widely used for assessing denture base materials and resin composites [21,23,25,26]. Our current study samples have demonstrated mechanical properties with values at the same magnitude compared with an earlier study of a similar setup [21].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Researches on other surface treatments is in progress in an attempt to improve adhesion and its durability in the oral cavity. (2)…”
Section: Tribochemical Silica Coatingmentioning
confidence: 99%
“…Phosphate esters can bond straight to non-silicabased ceramics such as zirconia. It has been stated that using this phosphate ester one can enhance the hydrolytic Figure 2: Silane coupling agents (2)…”
Section: Contemporary Trends and Future Development In Dentistrymentioning
confidence: 99%